Effect on Growth of Practical Diet Formulation with Non conventional Animal Protein Sources on Freshwater Catfish (Clarias magur) (Indian Journal of Extension Education, 2020)
The present study designed to evaluate the growth performance and survival of Clarias magur fed with non conventional animal protein sources. Four iso-nitrogenous experimental diets containing 35 per cent of protein level were prepared using ingredients such as Fish meal, Vermi meal, Chicken viscera, rice polish, wheat flour, vitamin and mineral mixture. Fishes fed with fishmeal based diet showed significantly higher final weight 204.93 g and the best specific growth rate 1.78. There was no significant difference for survival rate during the culture period with replacement of the fish meal component of practical diet with vermi meal and chicken viscera meal for magur. The study concluded that non-conventional animal protein like vermi meal and chicken viscera meal is an acceptable ingredient for the replacement of fish meal protein in practical diets of fishes